PENDIDIKAN ISLAM SEBAGAI INSTRUMEN INTERNALISASI NILAI SYARIAH MODERAT DALAM PENGUATAN MODERASI BERAGAMA GENERASI MUDA - Modesta Lartutul; Sofia Fahrany (Jurnal Studi Pesantren, 2026)
Islamic education holds a strategic function in shaping the religious character of the younger generation amid the social dynamics and cultural diversity of Indonesia. In the context of a pluralistic religious life, Islamic education not only serves as a medium for transmitting religious knowledge but also as an instrument for internalizing moderate sharia values grounded in the principles of wasathiyyah (balance), tawazun (justice), and tasamuh (tolerance). The central problem examined in this study is how Islamic education can function as an instrument for internalizing moderate sharia values to strengthen religious moderation among youth, as well as identifying the supporting and inhibiting factors that influence this process within educational settings. This study employs a literature review method with a descriptive-analytic and reflective approach. Data were collected from national and international academic journals, scholarly books, and policy documents related to Islamic education and religious moderation from the period 2018–2025. The approaches used include conceptual, comparative, and contextual analyses of value education theory, religious socialization, and models of moderation-based learning. The main obstacles identified include gaps between policy and teaching practices, limited teacher capacity, and the influence of digital media that lacks value-based guidance. The study concludes that Islamic education plays a crucial role as a social and ideological transformation agent in strengthening religious moderation among the younger generation. Through a humanistic, dialogic, and adaptive educational approach aligned with contemporary developments, moderate sharia values can be internalized deeply and sustainably, thereby fostering a peaceful, inclusive, and just religious life in Indonesia.